Sintesis Bukti untuk Pengembangan Model Pencegahan Anemia Remaja: Studi di Sulawesi Tengah - Taqwin Taqwin; Supriadi B Supriadi B; Fahmi Hafid; Yulianus Sudarman H Melangka; Nasrul Nasrul (Bomba: Jurnal Pembangunan Daerah, 2025)
Anemia among adolescent girls remains a major public health problem in Central Sulawesi, with substantial implications for regional human resource development. This study aimed to develop an integrated, evidence-based model for adolescent anemia prevention through a synthesis of findings from three field studies. Methods employed a descriptive–analytic integrative design combining a cross-sectional study on anemia determinants (Sigi District), an evaluative study on the implementation of anemia prevention programs (Donggala and Poso Districts), and a pre-experimental study assessing the effectiveness of multidisciplinary education (Donggala District), conducted between 2023 and 2025. A cumulative total of 809 adolescent girls aged 14–18 years were included. Results indicated that anemia prevalence ranged from 20.3% to 54.7%. Factors significantly associated with anemia included smoking behavior (OR=3.2; 95% CI: 1.1–8.7; ρ=0.025), low household income (OR=1.7; 95% CI: 1.0–2.9; ρ=0.039), undernutrition based on mid–upper arm circumference (OR=1.7; 95% CI: 1.1–2.6; ρ=0.011), and negative attitudes toward anemia prevention (OR=1.5; 95% CI: 1.0–2.3; ρ=0.043). Although iron–folic acid supplementation and food fortification programs have been implemented, their effectiveness remains limited due to low adherence. Multidisciplinary educational interventions significantly improved knowledge scores (from 6.46 to 7.90; ρ<0.001) and attitude scores (from 47.32 to 49.37; ρ=0.008). In conclusion, this evidence synthesis demonstrates that adolescent anemia prevention requires an integrated, cross-sectoral collaborative model that combines multidisciplinary education, strengthened adherence to nutrition programs, and family support. The proposed model contributes scientifically to the advancement of integrative anemia prevention approaches and provides policy-relevant evidence to inform regional health development strategies aimed at improving adolescent health and human resource quality in Central Sulawesi.